Hiérarchies urbaines et transitions énergétiques: une approche évolutive en Europe de 1800 à 2010 - Maximin Chabrol (VertigO)
This paper examines relationships between energy consumption and urban hierarchy evolution from 1800 to 2010 in France, Italy, Spain, England and Wales, Sweden and Netherland. This analysis is based on news energy consumption data including traditional and modern energy sources (Centre for History and Economics, Harvard) and on e-Geopolis database for population of urban areas 10 000 inhabitants and more (Moriconi F., CNRS, Avignon). The targets are exploration and recognition of the role of energy in urban dynamics, growth and structuration in hierarchies during 200 years. Then, this evolutionary approach asks about future urban dynamics in an energetic crises context.